KOMPARASI KINERJA KEUANGAN BANK NASIONAL DAN BANK ASING TAHUN 2010-2014 - Subuh, La; Zuhroh, Idah; Abdullah, Muhammad Faisal (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2016)
The purpose of this research was to know the profile of the financial performance of national banks and foreign banks and better financial performance between national bank with foreign banks. Analysis tool used was the test of normality and independent sample t-test. Research results showed that foreign banks are better than CAR aspect ratio, ROA and BOPO whereas national bank better than KAP and aspect ratio LDR. Then you coould take the conclusion that financial performance was better than foreign banks on the financial performance of national bank. Significant differences between the foreign banks and the national bank were at the ratio of CAR, ROA, and LDR, BOPO. Then that there was no significant difference in the ratio was KAP. Based on the determination of the level of health of the banks, both foreign and National BanksÂ were are on health predicate.